PELAKSANAAN PROGRAM KAMPUNG ZAKAT DALAM MENGATASI KURANGNYA PEMAHAMAN PENGETAHUAN ILMU AGAMA WARGA BLOK SILEDU DESA KEDUNGJAYA - liajamaliyah liyah; Siti Muspiah; Abdul Al Rahim A.S; Asep Fahmi Maulana; Rahmatullah (UI Cirebon (Universitas Islam Cirebon), 2023)
Community service activities carried out by IAIC students which were held at the beginning of August 29 - September 29 2022, located in the village of Kedung Jaya, Kedawung District, Cirebon Regency, have been very helpful for the community, especially in the Kedungjaya Village area, Kedawung District, Cirebon Regency. very kind and high enthusiasm. The implementation of the Kampung Zakat program in overcoming the lack of understanding of religious knowledge of the residents of the Siledu Block in Kedung Jaya Village is one way to increase religious understanding through regular weekly or monthly recitations at the mosque. Some of the supporters of these activities include: the participants in the implementation of the Kampung Zakat program have a very large willingness to gain knowledge of religious knowledge and know how to read the Koran well. Keywords: Program; Zakat Village; Religious.